Playing with the book : Victorian movable picture books and the child reader - Field, Hannah, 1984- (University of Minnesota Press, 2019)
"Playing with the Book analyzes novelty and movable publications for young children published from 1835 to 1914, specifically the panorama fold-out, the pop-up book, the dissolving-view book, and the mechanical book. Through the analysis of these unusual texts, Field encourages a reexamination of the relationship between pictures, words, and material format."--Provided by publisher.